1979
DOI: 10.2170/jjphysiol.29.669
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Squid Giant Axons in Hypotonic and Hypertonic Solutions

Abstract: Excitability of intracellularly perfused squid giant axons was maintained in hypotonic solutions (down to 300 mOSM) and in hypertonic solutions (up to about 10 OSM), when osmolalities of internal and external solutions were adjusted to be equal with glycerol, glucose, or sucrose. Molar concentrations of ions were kept constant during one series of experiments. The resting potential and the amplitude of the action potential did not change in both hypotonic and hypertonic solutions. With reduction of osmolality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The concentration of glycerol in the external and the internal solutions was gradually increased, keeping the osmolality of both solutions roughly equivalent in order not to lose the nerve activity (Kukita & Yamagishi, 1979a). The glycerol conentrations (in ~o (vol/vol) of the internal solutions were 10.5, 40.8 and 50.8 and those of the external solutions were 0, 34.2 and 44.2.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of glycerol in the external and the internal solutions was gradually increased, keeping the osmolality of both solutions roughly equivalent in order not to lose the nerve activity (Kukita & Yamagishi, 1979a). The glycerol conentrations (in ~o (vol/vol) of the internal solutions were 10.5, 40.8 and 50.8 and those of the external solutions were 0, 34.2 and 44.2.…”
Section: Methodsmentioning
confidence: 99%
“…While Hitchcock provided that evidence for the effectiveness of an intrathecal injection of cold saline (236), it was subsequently shown that the efficacy of hypertonic saline was due to the hypertonicity of the solution rather than to any thermal effect (237). Multiple other studies have shown various mechanisms including selective C-fiber blockade in cat dorsal rootlets with an increased concentration of chloride ion (238); decrease of the spinal cord water content and depressed lateral column-evoked ventral root response (174); change in the volume due to outflow of water across the membrane and ionic concentration changes (239); reduction in swelling or by osmotically induced fluid shifts, reducing pressure on the nerve, and producing a local anesthetic effect of the hypertonic solution (240); whereas some have illustrated an actual increase in tissue mass in the case of intravertebral tissue incubated in 10% sodium chloride solution (241). In contrast, Racz and colleagues (242) showed that the study of dural permeability in dogs demonstrated transdural calibration of hypertonic saline to occur very slowly, but resulted in the doubling of the cerebral spinal sodium concentration 20 minutes after extradural placement of 10% sodium chloride solution.…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, Hitchcock (53) showed the effectiveness of hypertonic saline was due to the hypertonicity of the solution, instead of any thermal effect. Multiple other effects described include selective C-fiber blockade in cat dorsal rootlets (54), reduction of spinal cord water content and depressed lateral col-umn-evoked ventral root response (55), volume change due to outflow of water across the membrane, and ionic concentration changes producing the effect on axonal function (56). Racz et al (57), in the dural permeability study in dogs demonstrated transdural equilibration of hypertonic saline to occur very slowly, with doubling of cerebrospinal sodium concentration to occur 20 minutes after extradural placement of 10% sodium chloride solution.…”
Section: Discussionmentioning
confidence: 99%